PSYCHOLOGICAL SERVICES FOR THE FAMILY: PROBLEMATIC ASPECTS AND MODERN APPROACHES (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article analyzes the theoretical and practical aspects of providing psychological services to the family. It also examines such pressing issues as family conflicts, communication problems, emotional coldness, and intergenerational conflicts, while analyzing effective methods of psychological support.